Competitive intelligence at Brazilian industrial maintenance departments (Journal of Information Systems and Technology Management, 2005)
The industrial maintenance activities, generally, were considered as more one problem to the organizations. This image needs to change in Brazil, because this sector is part of the companies supply chain, is responsible to maintain equipments reliability and availability and it is a generator of the companies costs. This responsibility increases in a country where the productive capacity is in the limit, demanding extra efforts and where increasing pressures for reductions of the costs and restrictions techniques and human beings are increasing, ask to paradigms changes. The present study had for purpose to identify main canals of captation of the information used by the Brazilian industrial maintenance professionals, demonstrating systematic use of Competitive Intelligence can bring technological advance and profit of competitive advantage. For this, a qualitative research was made, using as research instruments the Delphi method, interviews with professionals and an experimental delineation C.I- Competitive Intelligence in a department-pilot (automotive sector).The results had shown to the use of formal and informal sources in different frequencies of access and the fragility in these departments in the not-systematic use of C.I, harming the above-mentioned challenges.